Verification of Tropical Cyclogenesis Forecasts of the Korean Integrated Model for 2020-21 - Jung, Jiyoung; Chang, Minhee; Lee, Eun Hee; Sung, Mi-Kyung (American Meteorological Society, 2024)
Accurate tropical cyclogenesis (TCG) prediction is important because it allows national operational forecasting agencies to issue timely warnings and implement effective disaster prevention measures. In 2020, the Korea Meteorological Administration employed a self-developed operational model called the Korean Integrated Model (KIM). In this study, we verified fi ed KIM's TCG forecast skill over the western North Pacific. fi c. Based on 9-day forecasts, TCG in the model was objectively detected and classified fi ed as well-predicted, early formation, late formation, miss, or false alarm by comparing their formation times and locations with those of 46 tropical cyclones (TCs) from June to November in 2020-21 documented by the Joint Typhoon Warning Center. The prediction of large-scale environmental conditions relevant to TCG was also evaluated. The results showed that the probability of KIM detection was comparable to or better than that of previously reported statistics of other numerical weather prediction models. The intrabasin comparison revealed that the probability of detection in the Philippine Sea was the highest, followed by the South China Sea and central Pacific. fi c. The best TCG prediction performance in the Philippine Sea was supported by unbiased forecasts in large-scale environments. The missed and false alarm cases in all three regions had the largest prediction biases in the large-scale lower-tropospheric relative vorticity. Excessive false alarms may be associated with prediction biases in the vertical gradient of equivalent potential temperature within the boundary layer. This study serves as a primary guide for national forecasters and is useful to model developers for further refinement fi nement of KIM.